Investasi Syariah Pada Aset Riil UMKM Halal: Kedai Kopi, Ruang Digital, dan Reproduksi Identitas Perempuan Muda Pasca Shariatisme di Aceh - Agustinar; Mutia Sumarni; Dessy Asnita (FEBI IAIN Langsa, 2026)
Sharia investment in real assets constitutes a crucial pillar in strengthening the Islamic economy, particularly in relation to the sustainability of halal MSMEs. However, in much of the existing literature, Islamic investment is often narrowly understood as a purely financial activity, while the social and cultural dimensions that shape the value of real assets tend to be overlooked. Against this backdrop, this article examines coffee shops in Aceh as a form of halal MSME real asset that has developed within social and digital spaces following the implementation of Islamic law (Sharia).This study employs a qualitative case study approach. Data were collected through field observations, in-depth interviews with business owners, employees, and customers, as well as an analysis of coffee shops’ social media activities. The data were analyzed thematically to understand how Sharia investment value is constructed through everyday practices, social interactions, and digital representations. The findings reveal that coffee shops in Aceh function not merely as business entities but as spaces for the production of Sharia investment value grounded in social legitimacy, adherence to halal norms, and the strategic use of digital platforms. The reproduction of the syar’i-modern young female identity emerges as part of this process, operating as symbolic capital that fosters a sense of safety, social acceptance, and public trust. Nevertheless, the study also identifies tensions between symbolic imagery and managerial practices that may affect the sustainability of investment value.This research underscores that Sharia investment based on real assets should be understood as a dynamic and socially embedded socio-economic process, rather than merely a matter of financial returns.